2013
DOI: 10.1002/cctc.201300092
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Cooperative Catalysts for the Hydrogenation and Hydroformylation of Olefins

Abstract: Cooperative activation of substrates simultaneously by a (transition) metal and a protein residue is a common strategy in enzyme catalysis. Cooperative dinuclear catalysis for synthetic systems is relatively underdeveloped. Here, we focus on some examples of dinuclear hydrogenation and hydroformylation reactions, with the aim to stimulate the scientific community to develop more catalytic processes based on cooperative dinuclear systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 123 publications
(47 reference statements)
0
28
0
Order By: Relevance
“…Moreover, reaction rates and product distribution can be greatly affected by catalyst encapsulation. Interestingly, many catalytic reactions operate through a dinuclear mechanism or deactivate via a dinuclear pathway; by encapsulation of a transition metal complex, such decomposition pathways can be suppressed, leading to higher catalytic turnover numbers …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, reaction rates and product distribution can be greatly affected by catalyst encapsulation. Interestingly, many catalytic reactions operate through a dinuclear mechanism or deactivate via a dinuclear pathway; by encapsulation of a transition metal complex, such decomposition pathways can be suppressed, leading to higher catalytic turnover numbers …”
Section: Methodsmentioning
confidence: 99%
“…[4] Moreover,r eaction rates [5] and productd istribution [6] can be greatlya ffected by catalyst encapsulation. Interestingly, many catalytic reactions operate through ad inuclear mechanism [7] or deactivate via ad inuclearp athway; [8,9] by encapsulation of at ransition metal complex, such decomposition pathways can be suppressed, leading to higher catalytic turnover numbers. [10] In principle, an encapsulatione ventc ould also change the catalyticp athway of ar eaction, and as such can be used as as witch for ac atalytict ransformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the catalytic activity and selectivity of poly metallic catalyst are usually quite different from those of monometallic catalyst due to the synergistic effects [28][29][30][31]. However, there are also positive changes as the polymetallic catalyst consists of intermediates, which have both multi-metallic and monometallic compounds [32][33][34][35]. Klahn et al reported that the synergism of rhodium and rhenium in the complexes could dramatically enhance the catalytic performance in catalytic hydroformylation [36].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bimetallic complexes also play an important role in catalytic processes and novel abiotic molecule transformations. The concept of cooperative reactivity based on bimetallic catalysts [13][14][15] has lead to interesting applications such as asymmetric rearrangements, 16 ring opening reactions, 17 hydroalkoxylation of alkynes, 18 palladium-assisted C-X bond formation 19 and polymerizations. 20,21 Over the past decades compartmental ligands capable of coordinating multiple metal ions have been an intense area of research.…”
Section: Introductionmentioning
confidence: 99%